Gender equality in Romania: challenges and progress - Kamenitczky, Anna; Török, Ibolya (Észak-magyarországi Stratégiai Füzetek, 2024)
The aim of the study is to examine the achievement of the fifth Sustainable Development Goal, gender equality, in Romania. Using quantitative research techniques, the analysis focuses on a number of social and economic variables, comparing them to the EU average to give a more complete picture of the state of affairs in the nation. The findings demonstrate that while Romania has come a long way in the last several decades, there are still many obstacles in the way of gender equality. Based on the analysis, the study proposes recommendations for developing necessary strategies at the political and social levels.